THE RESISTANCE MOVEMENT OF INDONESIAN RAILWAYS WORKERS UNION (SPKA) AGAINST PT. KERETA API (PERSERO) IN POST REFORM - Hasanah, Rury; Kosandi, Meidi (PEOPLE: International Journal of Social Sciences, 2017)
The momentum of freedom after the New Order regime was utilized by railway workers to establish the Indonesian Railway Workers Union (SPKA) on 13 September 1999. The existence of SPKA is a place in voicing the demand for civil servant status and welfare improvement as a result of the Decree of the Minister of Transportation No.18 on Dismissal of Employees as Civil Servants of the Railway Service Company (PJKA). The return of civil servant status becomes more difficult to be realized when the company returns to PT. Kereta Api (Persero) thus strengthening the SPKA to conduct resistance movement against the company post-Reformation. This study aims to explain how the SPKA movement takes advantage of political opportunities in order to urge the government and company to fulfill their demands. The object of research that becomes the author’s focus is SPKA in launching the struggle movement demanding the return of civil servant status and the improvement of welfare.Using a documentary study and depth interview, this paper was built in descriptive-analytical way that helped the authors in explaining the political opportunities that were open after the Reformation. The author found four forms of political opportunity that exist and can be used by SPKA to conduct resistance movement that is reorganization of SPKA, openness of political access post Reformation, improvement of business climate in Indonesia, and management problem of the company. These four political opportunities correspond to the indicators of political opportunities in the social movement proposed by Tilly, Tarrow, and Schock.By utilizing the momentum of post-Reform freedom and political opportunities, the SPKA movement was able to pressure governments and corporations to meet their demands. This research is expected to be an academic contribution in the study of social movements and labor politics in the future.